Isolation and identification of indigenous wine yeasts and their use in alioholic fermentation - Zabukovec, Polona (Array, 2020)
Research background. In our study, spontaneous alcoholic fermentations were carried out to isolate non-Saccharomyces and Saccharomyces yeasts from grape must from different vine--growing regions in Slovenia. Additionally, the diversity of native Saccharomyces cerevisiae strains was evaluated during the process.Experimental approach. During spontaneous alcoholic fermentations the yeast population of non-Saccharomyces and Saccharomyces yeasts was sampled. We used eleven microsatellite markers to determine the genetic diversity of S. cerevisiae strains. In addition, different ratios of the indigenous strains of S. cerevisiae, Hanseniaspora uvarum and Starmerella bacillaris were tested for their possible use in alcoholic fermentation with inoculated yeasts by monitoring its course and measuring the concentration of aroma compounds in wine.Results and conclusions. Sequencing of the internal transcribed spacer (ITS) regions of ribosomal DNA showed that of 64 isolates, 46 strains represent S. cerevisiae and 18 strains belong to non-Saccharomyces yeasts. The identified non Saccharomyces yeast species were H. uvarum, Pichia kudriavzevii, Saturnispora diversa and S. bacillaris. The dendrogram grouped S. cerevisiae strains into 14 groups. The number of S. cervisiae strains isolated from the musts was 10 (Posavje), 11 (Podravje) and 25 (Primorska vine-growing region). On the other hand, the alcoholic fermentation with inoculated yeasts, in which the native S. cerevisiae strain predominated over H. uvarum and S. bacillaris, gave the most promising result due to the highest alcohol volume fraction, the lowest acetic acid concentration and significantly higher concentrations of volatile thiols 3-mercaptohexyl acetate (3MHA) and 3-mercaptohexan-1-ol (3MH), 2-methylpropanol, 2-methylbutanol, 3-methylbutanol and 2-phenylethanol) in the produced wine.